Chemical restraint of African mole‐rats (Fukomys sp.) with a combination of ketamine and xylazine. (29th May 2014) - Garcia Montero, Angelica; Burda, Hynek; Begall, Sabine
Abstract Objective To establish an accurate anaesthetic dose for chemical restraint of African mole‐rats using ketamine and xylazine. Study design Prospective nonrandomized laboratory study. Animals Sixteen adult Ansell's mole‐rats (Fukomys anselli) and eight giant mole‐rats (F. mechowii). Methods Fukomys anselli of different ages, sexes and reproductive status were systematically anaesthetized starting with an intramuscular injection of ketamine (2.5 mg kg−1) and increasing the doses in steps of 0.5 mg kg−1 until loss of the righting reflex (LRR) was observed. Xylazine was added to a constant dose of ketamine, starting at 0.5 mg kg−1 that was increased by 0.5 mg kg−1 in further trials. Once an effective combination was established and evaluated in F. anselli, it was also tested in F. mechowii. Heart and respiratory rates and rectal temperatures were measured during anaesthesia. anova for repeated measures and Student's t‐test were used to compare means. Results Chemical restraint was accomplished at a dose of 6 mg kg−1 ketamine combined with 2.5 mg kg−1 xylazine. LRR lasted on average mean 56 ± SD 19 minutes (F. anselli) and 140 ± 41 minutes (F. mechowii). Loss of pedal withdrawal reflex (LPR) lasted for 20 ± 15 minutes (F. anselli) and for 29 ± 2 minutes (F. mechowii), respectively. All animals recovered satisfactorily. Heart and respiratory rates were stable during anaesthesia, but rectal temperature fell significantly in F. mechowii after losing the righting reflex (LRR) from T1 (32.6 ± 0.6 °C) to T3 (30.4 ± 0.9 °C). Conclusions and Clinical relevance African mole‐rats (Bathyergidae) live in closed burrow systems under particular conditions (hypercapnia, hypoxia, stable temperature, humidity, darkness) and show several physiological adaptations. Injectable anaesthetics in the dose rates used in other rodents are not appropriate for use in these subterranean species. Here, a reliable protocol for chemical restraint is provided.